Risks of heightened human–wildlife conflict when subsidies disappear - Craig Packer (Trends in Ecology & Evolution, 2026)

Risk reduction, rangeland use, and the future of human–carnivore coexistence - Craig Packer (Conservation Biology, 2026)
Efforts to reduce livestock losses to large carnivores are widely regarded as essential for promoting human–carnivore coexistence. Predator‐proof enclosures, compensation programs, improved livestock guarding, and real‐time predator alert systems can reduce depredation and retaliatory killing while enhancing pastoralist livelihoods. However, reducing livestock production risks may also alter livestock management decisions in ways that increase grazing pressure or reshape land‐use patterns. I applied insights from moral hazard theory, rebound effects, and common‐pool resource governance to examine how carnivore conflict mitigation interventions may influence pastoral land use and long‐term conservation outcomes. Reduced predation risk may encourage herd expansion, higher stocking densities, or spatial expansion into areas previously avoided because of carnivore presence. Although such responses may improve household resilience, they may also increase competition for forage with wild herbivores, intensify habitat degradation, or shift conflict spatially rather than eliminate it. Because durable coexistence requires accounting for the broader incentives created by successful risk reduction, I developed a framework integrating carnivore conflict mitigation with grazing management, ecological monitoring, and livelihood diversification.

Female matrilines and male partnerships: long-term social dynamics of African lions - Craig Packer (Animal Behaviour, 2026)

Human-driven landscapes of fear for Africa's largest terrestrial predator in human-used conservation landscapes - Niels Mogensen; Craig Packer; Jens-Christian Svenning; Kasaine Sankan; Robert Buitenwerf (Biological Conservation, 2026)

Cross‐species transmission and evolutionary dynamics of canine distemper virus during a spillover in African lions of Serengeti National Park - Julie K. Weckworth; Brian W. Davis; Edward Dubovi; Nicholas Fountain‐Jones; Craig Packer; Sarah Cleaveland; Meggan E. Craft; Ernest Eblate; Michael Schwartz; L. Scott Mills; Melody Roelke‐Parker (Molecular Ecology, 2020)
The outcome of pathogen spillover from a reservoir to a novel host population can range from a “dead‐end” when there is no onward transmission in the recipient population, to epidemic spread and even establishment in new hosts. Understanding the evolutionary epidemiology of spillover events leading to discrete outcomes in novel hosts is key to predicting risk and can lead to a better understanding of the mechanisms of emergence. Here we use a Bayesian phylodynamic approach to examine cross‐species transmission and evolutionary dynamics during a canine distemper virus (CDV) spillover event causing clinical disease and population decline in an African lion population ( Panthera leo ) in the Serengeti Ecological Region between 1993 and 1994. Using 21 near‐complete viral genomes from four species we found that this large‐scale outbreak was likely ignited by a single cross‐species spillover event from a canid reservoir to noncanid hosts Crocuta crocuta ) could have acted as the proximate source of CDV exposure in lions. We report 13 nucleotide substitutions segregating CDV strains found in canids and noncanids. Our results are consistent with the hypothesis that virus evolution played a role in CDV emergence in noncanid hosts following spillover during the outbreak, suggest that host barriers to clinical infection can limit outcomes of CDV spillover in novel host species.

Mixed‐species groups of Serengeti grazers: a test of the stress gradient hypothesis - Lydia Beaudrot; Meredith S. Palmer; T. Michael Anderson; Craig Packer (Ecology, 2020)
Understanding the role of species interactions within communities is a central focus of ecology. A key challenge is to understand variation in species interactions along environmental gradients. The stress gradient hypothesis posits that positive interactions increase and competitive interactions decrease with increasing consumer pressure or environmental stress. This hypothesis has received extensive attention in plant community ecology, but only a handful of tests in animals. Furthermore, few empirical studies have examined multiple co‐occurring stressors. Here we test predictions of the stress gradient hypothesis using the occurrence of mixed‐species groups in six common grazing ungulate species within the Serengeti‐Mara ecosystem. We use mixed‐species groups as a proxy for potential positive interactions because they may enhance protection from predators or increase access to high‐quality forage. Alternatively, competition for resources may limit the formation of mixed‐species groups. Using more than 115,000 camera trap observations collected over 5 yr, we found that mixed‐species groups were more likely to occur in risky areas (i.e., areas closer to lion vantage points and in woodland habitat where lions hunt preferentially) and during time periods when resource levels were high. These results are consistent with the interpretation that stress from high predation risk may contribute to the formation of mixed‐species groups, but that competition for resources may prevent their formation when food availability is low. Our results are consistent with support for the stress gradient hypothesis in animals along a consumer pressure gradient while identifying the potential influence of a co‐occurring stressor, thus providing a link between research in plant community ecology on the stress gradient hypothesis, and research in animal ecology on trade‐offs between foraging and risk in landscapes of fear.

Genetic rescue of an isolated African lion population - Susan M. Miller; Dave J. Druce; Desiré L. Dalton; Cindy K. Harper; Antoinette Kotze; Craig Packer; Rob Slotow; Paulette Bloomer (Conservation Genetics, 2020)

Novel smacoviruses identified in the faeces of two wild felids: North American bobcat and African lion - Simona Kraberger; Laurel Serieys; Nicolas Fountain-Jones; Craig Packer; Seth Riley; Arvind Varsani (Archives of Virology, 2019)

Endemic infection can shape exposure to novel pathogens: Pathogen co‐occurrence networks in the Serengeti lions - Nicholas M. Fountain‐Jones; Craig Packer; Maude Jacquot; F. Guillaume Blanchet; Karen Terio; Meggan E. Craft (Ecology Letters, 2019)
Pathogens are embedded in a complex network of microparasites that can collectively or individually alter disease dynamics and outcomes. Endemic pathogens that infect an individual in the first years of life, for example, can either facilitate or compete with subsequent pathogens thereby exacerbating or ameliorating morbidity and mortality. Pathogen associations are ubiquitous but poorly understood, particularly in wild populations. We report here on 10 years of serological and molecular data in African lions, leveraging comprehensive demographic and behavioural data to test if endemic pathogens shape subsequent infection by epidemic pathogens. We combine network and community ecology approaches to assess broad network structure and characterise associations between pathogens across spatial and temporal scales. We found significant non‐random structure in the lion‐pathogen co‐occurrence network and identified both positive and negative associations between endemic and epidemic pathogens. Our results provide novel insights on the complex associations underlying pathogen co‐occurrence networks.

The diversity of population responses to environmental change - Fernando Colchero; Owen R. Jones; Dalia A. Conde; David Hodgson; Felix Zajitschek; Benedikt R. Schmidt; Aurelio F. Malo; Susan C. Alberts; Peter H. Becker; Sandra Bouwhuis; Anne M. Bronikowski; Kristel M. De Vleeschouwer; et al. (Ecology Letters, 2019)
The current extinction and climate change crises pressure us to predict population dynamics with ever‐greater accuracy. Although predictions rest on the well‐advanced theory of age‐structured populations, two key issues remain poorly explored. Specifically, how the age‐dependency in demographic rates and the year‐to‐year interactions between survival and fecundity affect stochastic population growth rates. We use inference, simulations and mathematical derivations to explore how environmental perturbations determine population growth rates for populations with different age‐specific demographic rates and when ages are reduced to stages. We find that stage‐ vs. age‐based models can produce markedly divergent stochastic population growth rates. The differences are most pronounced when there are survival‐fecundity‐trade‐offs, which reduce the variance in the population growth rate. Finally, the expected value and variance of the stochastic growth rates of populations with different age‐specific demographic rates can diverge to the extent that, while some populations may thrive, others will inevitably go extinct.

A sideways look at conservation and consistency in tourism policy - Amy Dickman; Craig Packer; Paul J. Johnson; David W. Macdonald (Conservation Biology, 2018)
Article impact statement : Wildlife‐based land management should be based on consistent principles for promoting sustainability.

A generalized approach for producing, quantifying, and validating citizen science data from wildlife images - Alexandra Swanson; Margaret Kosmala; Chris Lintott; Craig Packer (Conservation Biology, 2016)
Citizen science has the potential to expand the scope and scale of research in ecology and conservation, but many professional researchers remain skeptical of data produced by nonexperts. We devised an approach for producing accurate, reliable data from untrained, nonexpert volunteers. On the citizen science website www.snapshotserengeti.org , more than 28,000 volunteers classified 1.51 million images taken in a large‐scale camera‐trap survey in Serengeti National Park, Tanzania. Each image was circulated to, on average, 27 volunteers, and their classifications were aggregated using a simple plurality algorithm. We validated the aggregated answers against a data set of 3829 images verified by experts and calculated 3 certainty metrics—level of agreement among classifications (evenness), fraction of classifications supporting the aggregated answer (fraction support), and fraction of classifiers who reported “nothing here” for an image that was ultimately classified as containing an animal (fraction blank)—to measure confidence that an aggregated answer was correct. Overall, aggregated volunteer answers agreed with the expert‐verified data on 98% of images, but accuracy differed by species commonness such that rare species had higher rates of false positives and false negatives. Easily calculated analysis of variance and post‐hoc Tukey tests indicated that the certainty metrics were significant indicators of whether each image was correctly classified or classifiable. Thus, the certainty metrics can be used to identify images for expert review. Bootstrapping analyses further indicated that 90% of images were correctly classified with just 5 volunteers per image. Species classifications based on the plurality vote of multiple citizen scientists can provide a reliable foundation for large‐scale monitoring of African wildlife.

Asynchronous food‐web pathways could buffer the response of Serengeti predators to El Niño Southern Oscillation - A. R. E. Sinclair; Kristine L. Metzger; John M. Fryxell; Craig Packer; Andrea E. Byrom; Meggan E. Craft; Katie Hampson; Tiziana Lembo; Sarah M. Durant; Guy J. Forrester; John Bukombe; John Mchetto; et al. (Ecology, 2013)
Understanding how entire ecosystems maintain stability in the face of climatic and human disturbance is one of the most fundamental challenges in ecology. Theory suggests that a crucial factor determining the degree of ecosystem stability is simply the degree of synchrony with which different species in ecological food webs respond to environmental stochasticity. Ecosystems in which all food‐web pathways are affected similarly by external disturbance should amplify variability in top carnivore abundance over time due to population interactions, whereas ecosystems in which a large fraction of pathways are nonresponsive or even inversely responsive to external disturbance will have more constant levels of abundance at upper trophic levels. To test the mechanism underlying this hypothesis, we used over half a century of demographic data for multiple species in the Serengeti (Tanzania) ecosystem to measure the degree of synchrony to variation imposed by an external environmental driver, the El Niño Southern Oscillation (ENSO). ENSO effects were mediated largely via changes in dry‐season vs. wet‐season rainfall and consequent changes in vegetation availability, propagating via bottom‐up effects to higher levels of the Serengeti food web to influence herbivores, predators and parasites. Some species in the Serengeti food web responded to the influence of ENSO in opposite ways, whereas other species were insensitive to variation in ENSO. Although far from conclusive, our results suggest that a diffuse mixture of herbivore responses could help buffer top carnivores, such as Serengeti lions, from variability in climate. Future global climate changes that favor some pathways over others, however, could alter the effectiveness of such processes in the future.

Predatory senescence in ageing wolves - Daniel R. MacNulty; Douglas W. Smith; John A. Vucetich; L. David Mech; Daniel R. Stahler; Craig Packer (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1347–1356 Abstract It is well established that ageing handicaps the ability of prey to escape predators, yet surprisingly little is known about how ageing affects the ability of predators to catch prey. Research into long‐lived predators has assumed that adults have uniform impacts on prey regardless of age. Here we use longitudinal data from repeated observations of individually‐known wolves ( Canis lupus ) hunting elk ( Cervus elaphus ) in Yellowstone National Park to demonstrate that adult predatory performance declines with age and that an increasing ratio of senescent individuals in the wolf population depresses the rate of prey offtake. Because this ratio fluctuates independently of population size, predatory senescence may cause wolf populations of equal size but different age structure to have different impacts on prey populations. These findings suggest that predatory senescence is an important, though overlooked, factor affecting predator‐prey dynamics.

Serengeti real estate: density vs. fitness‐based indicators of lion habitat quality - Anna Mosser; John M. Fryxell; Lynn Eberly; Craig Packer (Ecology Letters, 2009)
Habitat quality is typically inferred by assuming a direct relationship between consumer density and resource abundance, although it has been suggested that consumer fitness may be a more accurate measure of habitat quality. We examined density vs. fitness‐based measures of habitat quality for lions in the Serengeti National Park, Tanzania. A 40‐year average of female reproductive success (yearling cubs per female) was best explained by proximity to river confluences, whereas patterns of productivity (yearling cubs per km 2 ) and adult female density (individuals per km 2 ) were associated with more general measures of habitat quality and areas of shelter in poor habitat. This suggests that density may not accurately distinguish between high‐quality ‘source’ areas and low‐quality sites that merely provide refuges for effectively non‐reproductive individuals. Our results indicate that density may be a misleading indicator of real estate value, particularly for populations that do not conform to an ideal free distribution.

The Conservation Relevance of Epidemiological Research into Carnivore Viral Diseases in the Serengeti - SARAH CLEAVELAND; TITUS MLENGEYA; MAGAI KAARE; DAN HAYDON; TIZIANA LEMBO; M. KAREN LAURENSON; CRAIG PACKER (Conservation Biology, 2007)
Recent outbreaks of rabies and canine distemper in wildlife populations of the Serengeti show that infectious disease constitutes a significant cause of mortality that can result in regional extirpation of endangered species even within large, well‐protected areas. Nevertheless, effective management of an infectious disease depends critically on understanding the epidemiological dynamics of the causative pathogen. Pathogens with short infection cycles cannot persist in small populations in the absence of a more permanent reservoir of infection. Development of appropriate interventions requires detailed data on transmission pathways between reservoirs and wildlife populations of conservation concern. Relevant data can be derived from long‐term population monitoring, epidemic and case‐surveillance patterns, genetic analyses of rapidly evolving pathogens, serological surveys, and intervention studies. We examined studies of carnivore diseases in the Serengeti. Epidemiological research contributes to wildlife conservation policy in terms of management of endangered populations and the integration of wildlife conservation with public health interventions. Long‐term, integrative, cross‐species research is essential for formulation of effective policy for disease control and optimization of ecosystem health.

Modeling the Effects of Trophy Selection and Environmental Disturbance on a Simulated Population of African Lions - KARYL L. WHITMAN; ANTHONY M. STARFIELD; HENLEY QUADLING; CRAIG PACKER (Conservation Biology, 2007)
Tanzania is a premier destination for trophy hunting of African lions (Panthera leo) and is home to the most extensive long‐term study of unhunted lions. Thus, it provides a unique opportunity to apply data from a long‐term field study to a conservation dilemma: How can a trophy‐hunted species whose reproductive success is closely tied to social stability be harvested sustainably? We used an individually based, spatially explicit, stochastic model, parameterized with nearly 40 years of behavioral and demographic data on lions in the Serengeti, to examine the separate effects of trophy selection and environmental disturbance on the viability of a simulated lion population in response to annual harvesting. Female population size was sensitive to the harvesting of young males (≥3 years), whereas hunting represented a relatively trivial threat to population viability when the harvest was restricted to mature males (≥6 years). Overall model performance was robust to environmental disturbance and to errors in age assessment based on nose coloration as an index used to age potential trophies. Introducing an environmental disturbance did not eliminate the capacity to maintain a viable breeding population when harvesting only older males, and initially depleted populations recovered within 15–25 years after the disturbance to levels comparable to hunted populations that did not experience a catastrophic event. These results are consistent with empirical observations of lion resilience to environmental stochasticity .

What limits the Serengeti zebra population? - Sophie Grange; Patrick Duncan; Jean-Michel Gaillard; Anthony R. E. Sinclair; Peter J. P. Gogan; Craig Packer; Heribert Hofer; Marion East (Oecologia, 2004)

Keeping the herds healthy and alert: implications of predator control for infectious disease - Craig Packer; Robert D. Holt; Peter J. Hudson; Kevin D. Lafferty; Andrew P. Dobson (Ecology Letters, 2003)
Predator control programmes are generally implemented in an attempt to increase prey population sizes. However, predator removal could prove harmful to prey populations that are regulated primarily by parasitic infections rather than by predation. We develop models for microparasitic and macroparasitic infection that specify the conditions where predator removal will (a) increase the incidence of parasitic infection, (b) reduce the number of healthy individuals in the prey population and (c) decrease the overall size of the prey population. In general, predator removal is more likely to be harmful when the parasite is highly virulent, macroparasites are highly aggregated in their prey, hosts are long‐lived and the predators select infected prey.